Smart sustainability : the role of AI in business intelligence - Mohanty, Madhusmita; Kumar, Rakesh; Kumar Panda, Rajeev; Ranjan Mallick, Rashmi; Walia, Kushal (Routledge, 2026)
This book emphasizes the contribution artificial intelligence (AI) can make to sustainable innovation and business intelligence. It highlights the evolution of smart sustainability and business intelligence practice through AI. AI significantly adds efficiency to sustainable business intelligence practices. This book supports a sustainable development agenda. The book is useful for policymakers, corporate leaders, researchers, industry professionals, and other stakeholders engaged in sustainable business practices.This book examines the different applications of AI - it can revolutionize green supply chain management, inventory management, and logistics management. Emerging trends are examined, along with problems and their fixes. Practitioners, companies, legislators, and researchers are provided with an implementation framework. In addition, ethical and environmental issues are covered, with a focus on sustainable and responsible behavior.To shed light on the efficacy of AI applications, the book offers sustainable start-up businesses real-world examples of its use. It also provides guidance on how to strategically incorporate AI into current frameworks for sustainable business practices. For professionals in business, technology, and sustainability, the book also helps with strategic planning. Professionals in waste reduction and resource management might also benefit from their insights. The book helps investors, entrepreneurs, and legislators make well-informed decisions. It increases public understanding of how augmented reality and virtual reality can support sustainable behaviors. The book promotes knowledge progress and sustainable practices across multiple industries by providing interdisciplinary viewpoints and acting as a bridge between theory and practice.
Keywords: Artificial intelligence -- Business applications.; Sustainable development.; elektronické knihy; electronic books